The depositional ontexts of the ships from Thonis-Heracleion, Egypt - Robinson, D (John Wiley and Sons, 2018)
Over 70 ancient vessels have been discovered by the Institut Européen d'Archéologie Sous‐Marine in the port‐city of Thonis‐Heracleion, Egypt. These were deposited both individually and in groups from the 8th to the 2nd century BC. This paper investigates the contexts of these vessels to suggest that a variety of explanations—shipwrecking, ritual deposition, abandonment, and structural reuse—account for their deposition. It also seeks to place these events within the changing landscape of Thonis‐Heracleion to understand the agency behind many of the decisions about what to do with old ships and boats at the end of their use‐life.